24=x⋅23⋅x

Rewrite the equation as x⋅23⋅x=24.

x⋅23⋅x=24

Combine x and 23.

x⋅23⋅x=24

Combine x⋅23 and x.

x⋅2×3=24

Raise x to the power of 1.

2(x1x)3=24

Raise x to the power of 1.

2(x1x1)3=24

Use the power rule aman=am+n to combine exponents.

2×1+13=24

Add 1 and 1.

2×23=24

2×23=24

Multiply each term in 2×23=24 by 32.

2×23⋅32=24⋅32

Simplify 2×23⋅32.

Cancel the common factor of 2.

Factor 2 out of 2×2.

2(x2)3⋅32=24⋅32

Cancel the common factor.

2×23⋅32=24⋅32

Rewrite the expression.

x23⋅3=24⋅32

x23⋅3=24⋅32

Cancel the common factor of 3.

Cancel the common factor.

x23⋅3=24⋅32

Rewrite the expression.

x2=24⋅32

x2=24⋅32

x2=24⋅32

Simplify 24⋅32.

Cancel the common factor of 2.

Factor 2 out of 24.

x2=2(12)⋅32

Cancel the common factor.

x2=2⋅12⋅32

Rewrite the expression.

x2=12⋅3

x2=12⋅3

Multiply 12 by 3.

x2=36

x2=36

x2=36

Take the square root of both sides of the equation to eliminate the exponent on the left side.

x=±36

Simplify the right side of the equation.

Rewrite 36 as 62.

x=±62

Pull terms out from under the radical, assuming positive real numbers.

x=±6

x=±6

The complete solution is the result of both the positive and negative portions of the solution.

First, use the positive value of the ± to find the first solution.

x=6

Next, use the negative value of the ± to find the second solution.

x=-6

The complete solution is the result of both the positive and negative portions of the solution.

x=6,-6

x=6,-6

x=6,-6

Solve Using the Square Root Property 24=x*2/3*x